Pembelajaran Problem Posing untuk Mengembangkan Kemampuan Komunikasi Matematis Siswa SMP - Rifaatul Mahmuzah; Aklimawati Aklimawati (Didaktik Matematika, 2016)
Mathematical communication skills is essential is owned by the student in the learning process, especially mathematics to solve mathematical problems that are non-routine and to convey thoughts, ideas and concepts in the form of mathematical symbols. Through communication students can convey their ideas, argues against any answers and provide feedback on the answers given by others, so that what is learned to be more meaningful. Therefore, it is very important to develop and improve mathematical communication in the learning process of mathematics. This study aims to assess the improvement of communication skills among students acquire mathematical learning and problem posing approach students who received conventional learning. This study was an experimental study using the design of pre-test post-test control group design. The population in this study were students of class VII SMP 1 Darul Imarah, Aceh Besar in the academic year 2016/2017. Samples were taken two classes, namely class VII-2 as an experimental class and class VII-1 as control class through random sampling techniques. The instrument used to collect research data in the form of mathematical communication ability test. The statistical test used to upgrade data of analyzed ability in mathematical communication is a two-lane Anova test. The results showed that the increase in mathematical ability of students who received learning by problem posing approach better than students who received conventional learning both overall and based on prior knowledge of students